Laryngeal schwannoma presented as globus sensation - KC, A.; Shakya, Dipesh; Nepal, A. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Laryngeal Schwannoma is an extremely rare with incidence of 0.1 – 1.5% in all benign laryngeal tumours making it difficult to diagnose. The most common anatomical site is the aryepiglottic fold, followed by the arytenoids, ventricular folds, and vocal cord. Most patients present with hoarseness, dysphagia or globus sensation.The present case report describes a 37 year old female patient with symptoms of globus sensation.